Current Situation of Thalassemia in Paktia Regional Hospital, Paktia, Afghanistan - Khaksar, Taj Mohammad; Totakhil, Noor Mohammad Wali; Mehrabi, Mir Ziaurahman (International Journal For Research In Biology & Pharmacy, 2021)
Background: Thalassemia is the most common hereditary disorder in the world including Afghanistan. The thalassemia is a major health problem all over the world, but this is particularly in the developing countries. Objectives: The present study aimed to determine the Current situation of thalassemia in Paktia Regional Hospital during the 21 months of 2019 and 2020. Methodology: This is a descriptive study conducted in Paktai Regional hospital in Paktia among patients diagnosed with thalassemia who require regular blood transfusions. Statistical analysis: The statistical analysis was performed by using the EPI INFO software package 6.04 version. The percentages were calculated for the various parameters which were under study. Results: Total of 137(100%) cases of thalassemia were included in the study. Amongst them 71 (51.82%) were males and 66(48.17%) were females. The majority cases 90(65.69%) were form urban area and the remaining 47(34.31%) were from rural area especially closed district. The majority of the cases were belonging to the younger 0-6 years of age group 105(76.64%) Conclusion: Since thalassemia is most common monogenetic inherited disease, and leads to fatal complications. Therefore, the data obtained from this study can be used by the public health authorities, to prepare a suitable action plan for reducing the burden of the disease and providing treatment and support to people already suffering from it. Families having thalassemic child should be educated about the disease. All members of the family should be screened for thalassemia trait and genetic counselling should be done.